2008
DOI: 10.1007/s10522-007-9123-5
|View full text |Cite
|
Sign up to set email alerts
|

Aging leads to increased levels of protein O-linked N-acetylglucosamine in heart, aorta, brain and skeletal muscle in Brown-Norway rats

Abstract: Changes in the levels of O-linked N-acetylglucosamine (O-GlcNAc) on nucleocytoplasmic protein have been associated with a number of age-related diseases such as Alzheimer's and diabetes; however, there is relatively little information regarding the impact of age on tissue O-GlcNAc levels. Therefore, the goal of this study was to determine whether senescence was associated with alterations in O-GlcNAc in heart, aorta, brain and skeletal muscle and if so whether there were also changes in the expression of enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 77 publications
2
64
0
Order By: Relevance
“…In rodent models, O-GlcNAc levels increase in multiple aged tissues (62). However, the molecular basis of the function of OGT in aging has not been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In rodent models, O-GlcNAc levels increase in multiple aged tissues (62). However, the molecular basis of the function of OGT in aging has not been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence shows a causal relationship between perturbations in O-GlcNAcylation and heart disease, cancer, AD, and diabetes (Chou et al, 1995;Love and Hanover, 2005;Liu et al, 2006;Dias and Hart, 2007;Fülöp et al, 2008), although the cellular mechanisms are far from understood. In contrast, recent studies suggest O-GlcNAcylation may be an endogenous, rapidly activated stress survival response (Zachara et al, 2004;Liu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Assays were performed as previously described (Gupta et al, 2010). Rats were placed in a test box for 9 min.…”
Section: Contextual Fear Conditioningmentioning
confidence: 99%
“…The majority of studies focusing on the role of O-GlcNAc in regulating cellular function have been in the context of chronic diseases including cancer, age-related diseases, diabetes, and diabetic complications (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, in 2004 Zachara et al (15) demonstrated for the first time that there was an acute increase in cellular O-GlcNAc levels in response to a range of stress stimuli and importantly that inhibition of this response increased cell death and conversely that augmenting this response increased tolerance of cells to stress.…”
mentioning
confidence: 99%